Pengembangan Rubrik Keterampilan Berpikir Kreatif dalam Memecahkan Masalah Matematika Siswa Kelas VIII SMP Attaufiq Jambi - Fiki Silvia; Risnita Risnita; Syaiful Syaiful (Universitas Jambi, 2015)
The purpose of this research was to know the characteristics of the developmental product of creative thinking skills rubricsin solving problem in mathematicsof the subject matter of Algebra for the 8-grade students of SMP Attaufiq Kota Jambi. This is also intended to know the eligibilityof the product, through Mathematic teacher assessment as a user and experts judgment (validation). This research and development was adopted the 4D model, that consists of four stages, i.e. define, design, develop, and disseminate. Based on the teachers assesment and experts judgement can be concluded that the developed rubrics is already valid and can to be apply for the 8-grade students on junior high school.